Effects of Vegetarian Diets on Blood Lipids: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 10 (October 2015) - Wang, Fenglei; Zheng, Jusheng; Yang, Bo; Jiang, Jiajing; Fu, Yuanqing; Li, Duo
Abstract : Background: Vegetarian diets exclude all animal flesh and are being widely adopted by an increasing number of people; however, effects on blood lipid concentrations remain unclear. This meta‐analysis aimed to quantitatively assess the overall effects of vegetarian diets on blood lipids. Methods and Results: We searched PubMed, Scopus, Embase, ISI Web of Knowledge, and the Cochrane Library through March 2015. Studies were included if they described the effectiveness of vegetarian diets on blood lipids (total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and triglyceride). Weighted mean effect sizes were calculated for net changes by using a random‐effects model. We performed subgroup and univariate meta‐regression analyses to explore sources of heterogeneity. Eleven trials were included in the meta‐analysis. Vegetarian diets significantly lowered blood concentrations of total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and non–high‐density lipoprotein cholesterol, and the pooled estimated changes were −0.36 mmol/L (95% CI −0.55 to −0.17; P <0.001), −0.34 mmol/L (95% CI −0.57 to −0.11; P <0.001), −0.10 mmol/L (95% CI −0.14 to −0.06; P <0.001), and −0.30 mmol/L (95% CI −0.50 to −0.10; P =0.04), respectively. Vegetarian diets did not significantly affect blood triglyceride concentrations, with a pooled estimated mean difference of 0.04 mmol/L (95% CI −0.05 to 0.13; P =0.40). Conclusions: This systematic review and meta‐analysis provides evidence that vegetarian diets effectively lower blood concentrations of total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and non–high‐density lipoprotein cholesterol. Such diets could be a useful nonpharmaceutical means of managing dyslipidemia, especially hypercholesterolemia.